Selective Diacetoxylation of Disubstituted 1,2,3-Triazoles through Palladium-Catalyzed C–H Activation - Yang, Jianhua; Zhao, Fen; Liu, Yaowen; Luo, Fang; Cheng, Huiling; Jiang, Yubo (Synlett, 2018)
A simple and efficient selective diacetoxylation of 1,4-disubstituted 1,2,3-triazoles by Pd-catalyzed C–H bond activation is described. PhI(OAc)2 was used as an acetyloxy source to convert aromatic sp2 C–H bonds into C–O bonds with high selectivity by employing a 1,2,3-triazole ring as an elegant directing group. A range of 1,2,3-triazoles bearing two acetyloxy groups can be readily synthesized by the reaction.
Keywords: palladium catalysis; regioselectivity; acetoxylation; diacetoxytriazoles; C–H activation